2007
DOI: 10.1038/sj.onc.1210800
|View full text |Cite
|
Sign up to set email alerts
|

JAK kinases overexpression promotes in vitro cell transformation

Abstract: Constitutive activation of the JAK-STAT pathway is frequent in cancer and contributes to oncogenesis. Here, we took advantage of the Ba/F3 cell line, a murine proB cell line dependent on IL-3 for growth, to analyse mechanisms of constitutive STAT activation in vitro. Cytokineindependent and tumorigenic Ba/F3 cell lines were derived from a two-step selection process. Cells transfected with a defective IL-9 receptor acquire IL-9 responsiveness during a first step of selection, and progress after a second selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
1
32
0
1
Order By: Relevance
“…16 In this study, we show that 80% of the autonomous BaF3 clones, selected in our in vitro model, acquired activating point mutations in the kinase or pseudokinase domain of JAK1. These JAK1 mutations provide cells with tumorigenic potential by inducing constitutive activation of the JAK-STAT pathway, which supports their autonomous proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 In this study, we show that 80% of the autonomous BaF3 clones, selected in our in vitro model, acquired activating point mutations in the kinase or pseudokinase domain of JAK1. These JAK1 mutations provide cells with tumorigenic potential by inducing constitutive activation of the JAK-STAT pathway, which supports their autonomous proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The first step requires spontaneous upregulation of JAK1, while the mechanism involved in the second step of transformation is not known. 16 As constitutive phosphorylation of JAK1 was detectable in autonomous clones, 14 we systematically sequenced JAK1 from autonomous clones and found that the vast majority of them (139 of 164) were heterozygous for a single de novo mutation. Altogether, 25 different missense mutations were identified as listed in the Online Supplementary Table S1 and Online Supplementary Figure S1.…”
Section: De Novo Mutations In Kinase and Pseudokinase Domain Of Jak1 mentioning
confidence: 99%
See 2 more Smart Citations
“…51 In addition overexpression of several non-mutated JAK proteins, including JAK2, was shown to promote hematopoietic transformation to cytokine independence. 128 The phenotype induced by exon 12 mutants of JAK2 is more restricted to erythrocytosis, without the abnormal megakaryocyte clusters seen in the classical MPNs. 18 These in vivo data indicate that a difference must exist between signaling by JAK2 V617F and exon 12 JAK2 mutants.…”
Section: Jak2 Mutantsmentioning
confidence: 99%